Lao Peoples Democratic Republic energy sector assessment, strategy, and road map. ([Manila] Asian Development Bank, 2019)
Expanded access to modern and affordable forms of energy and more efficient use of energy resources will be essential for the Lao PDR to achieve its socioeconomic development goals. This publication provides an overview of Lao PDRs energy sector, examines its performance, the challenges it faces, and the governments energy strategy. It also reflects on lessons learned from past ADB assistance and proposes potential areas for future support.
Keywords: Natural resources -- Lao Republic; Economic development -- Lao People Democratic Republic; Renewable energy resources; Electronic books